The final countdown to site selection for Canada's nuclear waste geologic repository. (2nd January 2023) - Braden, Zoe; Macfarlane, Allison
ABSTRACT: Selecting a site to build a deep geologic repository for high-level nuclear waste is a process fraught with social tension and few countries have managed to do so successfully. Canada is poised to be next, with a site selection decision due in 2024. Two potential sites are under consideration, one in northern Ontario and one in southern Ontario, each with different geologic settings and different social and economic landscapes. We review the consent-based process that has led to this point, the complexities involved in expressing consent in Canada, and some of the hurdles that remain.